Pyrosequencing-based quantitative identification of p16 methylation in diffuse large b-cell lymphoma at two centres in the east coast of malaysia - Mohd. Ridah, Lailatul Jalilah; Ismail, Aziah; A. Talib, Norlelawati; Muhammad, Siti Aesah @ Naznin; Hussain, Faezahtul Arbaiyah; Zainuddin, Norafiza (Universiti Sains Malaysia, 2016)
Introduction: Methylation of promoter region of p16 leading to gene silencing has been implicated in a wide range of malignancies including lymphomas. In diffuse large B cell lymphoma (DLBCL) particularly, a varying percentage of epigenetic inactivation of p16 promoter region was observed ranging from 16 - 54%. However, quantitative analysis of p16 promoter methylation in DLBCL has not been extensively studied in Malaysia. Objective: This study aims to quantitatively analyse p16 methylation in DLBCL samples using pyrosequencing technique. Methods: Genomic DNA was extracted from 16 formalin-fixed paraffin-embedded lymphoma tissue blocks from patients diagnosed with DLBCL. Samples were retrieved from Hospital Tengku Ampuan Afzan, Pahang and Hospital Universiti Sains Malaysia, Kelantan. Primers were designed to amplify bisulfite-treated DNA targeting p16 promoter region. Methylation status of 7 CpG sites was determined by pyrosequencing. Results: All the 16 samples studied showed promoter methylation of p16. The range of mean methylation percentage was between 18 to 81%. Conclusion: The present study has successfully measured the level of methylation of p16 in all 7 CpG sites despite the limitation in sample size. Since p16 methylation is a common event in our series of DLBCL cases, it is worth including a larger sample size in future studies to increase the chance of finding a significant correlation with clinical parameters.